The semisynthetic landscape of aphidicolin: inspiration towards leishmanicidal compounds - Santos, Gabriela B.; Almeida, Marília O.; Cardoso, Iara A.; Manfrim, Viviane; Chagas, Fernanda O.; Toledo, Juliano S.; Pinzan, Camila C.; Araujo, Alexandre Suman De [UNESP]; Cruz, Angela K.; Pupo, Monica T.; Emery, Flavio S. (Sociedade Brasileira de Química, 2014)
Recent studies have shown that aphidicolin, a secondary metabolite of the endophytic fungus Nigrospora sphaerica, has high activity against the protozoan Leishmania major. Despite its promising leishmanicidal potential, aphidicolin presents a therapeutically unsuitable physico-chemical and pharmacokinetic profile. In this sense, a review of the literature shows the limited types of modification for this terpene. In addition, it gives an idea about the molecular properties of the compounds produced and which were correlated to leishmanicidal derivatives. This analysis provided us a rationale for the development of an oxime derivative. We synthesized the oxime-aphidicolin and a series of derivatives for a preliminary evaluation of the structural requirements for the leishmanicidal activity of aphidicolin and its semisynthetic derivatives. Eight compounds have been synthesized and tested against different species of the Leishmania protozoa. The preliminary evaluation demonstrated high leishmanicidal activity for aphidicolin, while the oxime derivative shows moderate selectivity for the L. braziliensis species, which is commonly found in several South American countries. None of the compounds showed cytotoxicity against mammalian cells.

Recentes estudos demonstraram que afidicolina, metabólito secundário do fungo endofítico Nigrospora sphaerica, apresenta alta atividade contra o protozoário Leishmania major. Apesar do promissor potencial leishmanicida, a afidicolina apresenta propriedades físico-químicas e perfil farmacocinético inadequado para terapêutica. Neste sentido, uma revisão da literatura apresenta as limitadas modificações para este terpeno e ainda traz informações sobre as propriedades moleculares dos compostos já descritos e sua correlação com compostos leishmanicidas. Essa revisão forneceu uma análise racional para o desenvolvimento do derivado oxima. Uma série de derivados da afidicolina bem como o análogo oxima foram sintetizados para avaliação preliminar dos requisitos estruturais para atividade leishmanicida da afidicolina e seus derivados semi-sintéticos. Oito compostos foram sintetizados e testados contra diferentes espécies de Leishmania. A avaliação preliminar demonstrou alta atividade leishmanicida da afidicolina enquanto que o derivado oxima apresenta moderada seletividade contra a espécie L. braziliensis, endêmica em diversos países da América do Sul. Nenhum dos compostos apresentou citotoxicidade contra células de mamíferos.
Keywords: diterpenes; aphidicolin; Leishmania spp.; semisynthesis; molecular properties